2017
DOI: 10.5056/jnm16135
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Irritable Bowel Syndrome

Abstract: Traditionally, irritable bowel syndrome (IBS) has not been regarded as an organic disease, and the pathophysiology of IBS is heterogeneous. Currently, the diagnosis of IBS is based upon the Rome diagnostic criteria. The performance of these criteria is only modest in predicting IBS, and moreover their validation is lacking. Additionally, as functional symptoms are common in the general population, healthy controls or volunteers are difficult to define and there is currently no definition of "normal" in the Rom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 47 publications
0
32
0
1
Order By: Relevance
“…By contrast, in the study of Ringel‐Kulka and colleagues (), SCFAs were found to discriminate IBS from healthy controls only when based on the subtype. Therefore, although they are recognized as biomarkers for IBS (Kim et al ., ), SCFAs require further study to elucidate their actual role in IBS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in the study of Ringel‐Kulka and colleagues (), SCFAs were found to discriminate IBS from healthy controls only when based on the subtype. Therefore, although they are recognized as biomarkers for IBS (Kim et al ., ), SCFAs require further study to elucidate their actual role in IBS.…”
Section: Introductionmentioning
confidence: 99%
“…IBS is conventionally classified into four subtypes according to bowel habits: IBS with constipation (IBS-C), IBS with diarrhea (IBS-D), and IBS with alternating constipation and diarrhea (mixed IBS, IBS-M) as well as unsubtyped IBS (IBS-U) (Mearin et al, 2016). The diverse mechanisms underlying the pathophysiology of IBS subtypes remain unknown, and validated mechanistic biomarkers for the IBS subtypes are not available (Kim et al, 2017). IBS-subtype specific alterations of the intestinal microbiota have been reported (Malinen et al, 2005;Kassinen et al, 2007;Lyra et al, 2009;Carroll et al, 2010;Pozuelo et al, 2015;Tap et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, we found no significant differences with respect to the fecal propionic/butyric ratio and propionic acid-butyric acid in patients with IBS-D and HCs. Others also agreed that fecal SCFAs could be used as a biomarker for the discrimination of IBS from HCs [31]. A recent systematic review and meta-analysis demonstrated that fecal butyrate was increased in IBS-D patients in comparison to HCs, and fecal propionate and butyrate could be used as biomarkers for IBS diagnosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder, associated with a range of symptoms including abdominal pain or bloating and altered bowel habits [1][2][3][4]. It affects around 10-15% of the population [5], women being more frequently affected with a two-to threefold increase [6].…”
Section: Introductionmentioning
confidence: 99%